1997
DOI: 10.1002/(sici)1096-8628(19970303)69:1<65::aid-ajmg12>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Hypoplastic thymus and T-cell reduction in EECUT syndrome

Abstract: We report on a patient with EEC/EECUT syndrome and concomitant hypoplasia of the thymus and reduction of T cells in secondary lymphatic organs. The patient was born prematurely at 35 weeks of gestational age and exhibited ectodermal dysplasia, ectrodactyly, cleft palate and urinary tract abnormalities. On the left side, a large ureterocele was present. On the right side, an atretic ureter was found. Both conditions had led to intrauterine hydronephrosis, renal dysplasia, oligohydramnios, pulmonary hypoplasia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A prior clinical observation suggests an expanded spectrum for the EECUT syndrome spectrum of disorders ( e ctrodactyly, e ctodermal dysplasia, c lefting, u rinary t ract abnormalities) to include thymic involvement with a designated name EECUT plus syndrome [Frick et al, ]. We report a male child whose clinical features overlap with EECUT plus syndrome and who has a novel de novo mutation in TP63 , providing molecular evidence for mutations in TP63 and EECUT plus syndrome.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…A prior clinical observation suggests an expanded spectrum for the EECUT syndrome spectrum of disorders ( e ctrodactyly, e ctodermal dysplasia, c lefting, u rinary t ract abnormalities) to include thymic involvement with a designated name EECUT plus syndrome [Frick et al, ]. We report a male child whose clinical features overlap with EECUT plus syndrome and who has a novel de novo mutation in TP63 , providing molecular evidence for mutations in TP63 and EECUT plus syndrome.…”
Section: Introductionmentioning
confidence: 52%
“…Genitourinary abnormalities include structural kidney or ureteral malformations which have resulted in expansion of the EEC syndrome to EECUT syndrome [Hecht, ]. A report was published in 1997 describing a newborn male child with EEC‐related malformations including cystic enlargement of both kidneys secondary to a large ureterocele, short palpebral fissures, hypoplastic finger and toe nails, absent eyelashes, eyebrows, scalp hair and lanugo, bilateral syndactyly of fourth and fifth toes, genital abnormalities, and hard palate cleft [Frick et al, ]. Hypoplastic lungs and cystic kidneys were detected on antenatal ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…But details on ML subtypes and discussions on the significance of p63 overexpression in MLs were not provided (25). In humans, heterozygous germline p63 mutations have been described in EEC syndrome, in which a single case has been described with thymic hypoplasia (26) although no lymphoid or thymic abnormalities have been described in p63-null mice (16, 27). There is also another case study examined a sporadic incident of EEC syndrome (ectrodactyly ectodermal dysplasia-clefting syndrome) of complete form of the anomaly with late onset of non-Hodgkin's lymphoma (28).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that p63 and p73 show epitheliotropic expression in many tissues, suggesting their fundamental roles in the maintenance of epithelial cell identity (Di Como et al 2002;Green et al 2003;Kamiya et al 2004). The functional relevance of such p53 family members of the human thymus is presumed in previous reports that, for example, mutations of the p63 gene cause ectrodactyly-ectodermal dysplasia cleft lip/palate (EEC) and EEC-related syndromes, some of which exhibit histological abnormalities of the thymus and prominent depletion of cells in T-zones of the lymph nodes (Frick et al 1997;Celli et al 1999;Brunner et al 2002). We have recently reported nuclear localization of p63 and p73 in human TECs, which are capable of regulating cell adhesion through ICAM-1/LFA-1 interaction (Ichimiya et al 2002;Kikuchi et al 2004).…”
Section: Discussionmentioning
confidence: 99%